Tragic error and the Augustinian Morals - Eksen, Kerem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The aim of the present thesis is to reconsider the notion of “tragic error” from a philosophical perspective and by concentrating mainly on the thought of Augustine. Our starting-point has been the differences between the ways in which, on the one hand the classical Greek tragedians, and on the other the critics and dramatists of seventeenth and eighteenth centuries problematized human action. While Greek tragedy was based on what we have called an “objective” notion of error (focusing mainly on the objective changes that a given action creates in the universe), the Renaissance and post- Renaissance mentality adopted a “subject-centered” standpoint and a “subjective” notion of error (laying emphasis on the conditions and qualities of the agent of an act). Augustine is the main figure of our project, since his work sheds light on the shift from an “objective” conception of error to a “subjective” one. On the basis of this idea, we presented the two major dimensions of Augustine’s ethical theory: On the one hand, we focused on the “subjective” aspects of Augustine’s theory of sin, in order to see how he defines sin on an individual basis; and on the other hand, we studied the “objective” aspects of his theory, in order to see how Augustine relates the experience of error to an “objective” condition of fallibility. We have argued that these two aspects of Augustine’s thought lie at the basis of Renaissance tragedy and that, in this sense, tragic poets like Racine and Shakespeare are post-Augustinian.
Keywords: Literature -- History and criticism.